TINJAUAN PRINSIP ‘ADALAH TERHADAP KONTESTASI PASAR TRADISIONAL DENGAN PASAR MODERN DI BARANTI KAB. SIDENRENG RAPPANG - Ulya Hatta; Damirah Damirah; Suarning Suarning; Muliati Muliati; Andi Bahri (IAIN BONE, 2026)
Market contestation refers to the competition between traditional and modern markets in Baranti to attract consumers. This study aims to understand the reality of market contestation and the application of the ‘adalah principle in market competition. The research method used is qualitative descriptive, with field research as the primary approach. Data sources include primary and secondary data. Data analysis techniques include data presentation, data reduction, and conclusion drawing. The findings of this study are: (1) The competition between traditional and modern markets in Baranti, Sidenreng Rappang Regency is influenced by the existence of both market types, competition, and socio-cultural impacts. Although modern markets offer more comfort, traditional markets remain vital to the local community. Both markets can complement each other and provide significant benefits to Baranti residents if managed properly. (2) Markets in Baranti implement the ‘adalah principle in competition through three ways: enforcing fair pricing, avoiding uncertainty (gharar), and promoting ethical trading freedom. (3) The analysis of the ‘adalah principle can be realized by applying principles of transparency, objectivity, and accountability